Optimization of child-friendly green open space for Brebes’ positioning as a child-friendly regency - Intan Putri Cahyani; Eky Erlanda Edel; Yulius Dala Ngapa (Masyarakat, Kebudayaan dan Politik, 2019)
The Provision of Green Open Spaces (GOS) as a playground for children as well as introducing environmental awareness is a concern in various regions. GOS is a facility from the local government to fulfil children’s rights in terms of growing and developing in a healthy and safe environment, especially for Brebes, which has declared themselves to be a Child-Friendly Region. Nevertheless, currently, Brebes only has 12 GOSs, which is around 15 per cent of its total area. It hampered by the contradictions between the standard requirements for GOS development and the alteration of land functions due to urbanisation in addition to the lack of community involvement in spatial planning between 2012 and 2017. The purpose of this study is to examine the optimisation of GOS in Brebes Regency from the perspective of environmental communication towards the positioning of Brebes as a child-friendly city; this research is a qualitative descriptive study using ethnographic methods and an environmental communication approach. The qualitative data obtained through in-depth interviews, observations and the documentation of eight informants. The findings show that GOS Brebes currently functions as a media for child development. There are some obstacles in terms of optimising the spaces in Brebes because there are some behaviours that are not child-friendly and/or environmentally friendly. Furthermore, the GOS conditions in Brebes generally fulfil the principles of Child-Friendly Spaces (CFS) as the indicators of the optimal performance of GOS. In addition, communication, resources, disposition and bureaucratic structure are important factors in terms of optimising child-friendly GOS in Brebes. Finally, cooperation between the government and the community members to create an ideal child-friendly GOS should be supported by clear regulations and policies, as well as communicated through the media appropriately and sustainably.